Predictors of turnover intentions in learning‐driven and demand‐driven international assignments: The role of repatriation concerns, satisfaction with company support, and perceived career advancement opportunities - Stahl, Günter K.; Chua, Chei Hwee; Caligiuri, Paula; Cerdin, Jean‐Luc; Taniguchi, Mami (Human Resource Management, 2009)
AbstractInternational assignments have become an important part of managers' careers and are considered one of the most effective leadership development tools. Yet, studies consistently show that companies fail to integrate international assignments with long‐term career development and succession planning and that a substantial percentage of expatriates leave the company upon completion of the international assignment. A total of 1,779 international assignees participated in a study that examined the factors associated with expatriate turnover intentions. The results indicate the importance of differentiating between two types of international assignments—developmental (or learning‐driven) and functional (or demand‐driven)—to understand expatriates' turnover intentions. While we found turnover intentions to vary depending on whether assignments are developmental or functional, the three sets of predictors of turnover intentions are similar. They are (1) lower satisfaction with company support, (2) higher repatriation concerns, and (3) lower career advancement opportunities within the company (relative to opportunities available outside the company). We discuss the implications for research and practice. © 2009 Wiley Periodicals, Inc.